2009
DOI: 10.1088/0953-8984/21/27/275502
|View full text |Cite
|
Sign up to set email alerts
|

Bulk and surface sp half-metallic ferromagnetism in alkali metal pnictides with rocksalt structure: a first-principles calculation

Abstract: Recently, sp half-metallic ferromagnetism in alkali metal/alkaline earth pnictides (I/II-V) with zinc blende structure was predicted by first-principles calculations (Sieberer et al 2006 Phys. Rev. B 73 024404). To search for half-metallic ferromagnets with a more stable structure in alkali metal pnictides MX (M  = Li, Na, K; X =  N, P, As), we apply here first-principles all-electron and pseudopotential-method-based density functional theory to investigate the electronic and magnetic properties of these compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…13 These results were independently confirmed by Yan, 14 and by Gao and collaborators who have also shown that among the alkali metal phosphides and arsenides, only KP and KAs are half-metallic ferromagnets. 15 Finally, Gao et al have also studied the alkali-metal sulfides (Li, Na, K)S which exhibited a total spin magnetic moment of 1 B as expected by the SP rule for both the ZB and the energetically-favored RS structures. 16 Gao and collaborators have studied a series of alkalineearth metal compounds with the IVth column elements and found that all CaSi, CaGe, CaC, SrC and BaC in the ZB structure are half-metals.…”
Section: Overview Of Recent Literaturementioning
confidence: 97%
“…13 These results were independently confirmed by Yan, 14 and by Gao and collaborators who have also shown that among the alkali metal phosphides and arsenides, only KP and KAs are half-metallic ferromagnets. 15 Finally, Gao et al have also studied the alkali-metal sulfides (Li, Na, K)S which exhibited a total spin magnetic moment of 1 B as expected by the SP rule for both the ZB and the energetically-favored RS structures. 16 Gao and collaborators have studied a series of alkalineearth metal compounds with the IVth column elements and found that all CaSi, CaGe, CaC, SrC and BaC in the ZB structure are half-metals.…”
Section: Overview Of Recent Literaturementioning
confidence: 97%
“…Recently, one kind of HMF materials has been predicted which are related to s and p electrons [4][5][6][7]. The d 0 magnetic system based on s and p electrons was theoretically confirmed in a number of perfect crystals such as ideal bulk I A -V, I A -IV, II A -V and II A -IV compounds [8][9][10][11][12], molecular crystals containing O 2 or N 2 molecules as structural units, carbon based materials such as graphite and grapheme nanoribbons, and magnetic materials obtained by doping nonmagnetic sp compounds (chalcogenides, pnictides, and borides of nontransition sp elements), or nanostructures (BN, AIN, and MgO nanotubes) with nonmagnetic sp impurities or nanostructures involving structural vacancies or topological defects (see recent reviews [13] and [14]). This class of magnetic systems not containing transition metal or rare earth ions has been predicted to have a different mechanism of the magnetism, which is related to s and p rather than to d or f atomic orbitals.…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, A few studies have been performed on the surface properties of CaC [29] and the surface properties of the Ca and Sr nitrides and interfaces with binary semiconductors [30].…”
Section: Introductionmentioning
confidence: 99%